Implementación de un sistema de esterilización de envases para productos alimenticios en el Centro Experimental Salache de la UTC - Andrango Chacha, Cristian Fernando (2017)
The present research work has the purpose of implementing a sterilization system of containers through saturated steam for food products in the Salache experimental center of the Technical University of Cotopaxi in conjunction with the Electromechanical Engineering and Agroindustrial Engineering Careers, with The use of an exhausting tunnel, using suitable technologies that allow to be at the same time with the modern industrialization and in turn that this production center does not have an equipment capable of sterilizing the containers before filling and closing hermetic, to improve quality in food production. The methodology for the development of the proposal was divided into three parts, the first one is based on the application of the analytical method to obtain the adequate theoretical foundation and proceed to the use of the second method which is the synthetic, allowing the analysis and selection of materials used in the construction of the machine, to finally apply the quasi-experimental method for the design and construction of a computer capable of satisfying the requirements and needs of the university, because the said sterilization system was based on a tunnel exhausting used in the food industry. For the preparation of the machine was designed first the heating system where the saturated steam will circulate for sterilization, followed by the selection of elements suitable for the development of the electrical system that allows controlling the speed of the band where they are transported The containers and the temperature of the exhausted chamber by means of an electrovalve allowing the opening or closing of the steam when the temperature decreases or exceeds the ranges programmed in the temperature controller. In addition, in order to obtain the transportation system, the elements in the exhaust tunnel were considered, which allowed the selection of bearings, drive shaft and drive and drive rollers. This system complies with each of the standards governing the food industry (Standards UNE-EN 1672-2 and UNE-EN ISO 12100), in order to be suitable for the sterilization of packaging used in food production.